Strategy for communicating benefit-risk decisions: a comparison of regulatory agencies' publicly available documents - Leong Wai Yeen, James; Salek, Sam; Walker, Stuart (Frontiers in Pharmacology, 2014)
The assessment report formats of four major regulatory reference agencies, US Food and Drug Administration, European Medicines Agency, Health Canada, and Australia’s Therapeutic Goods Administration were compared to a benefit-risk (BR) documentation template developed by the Centre for Innovation in Regulatory Science and a four-member Consortium on Benefit-Risk Assessment. A case study was also conducted using a US FDA Medical Review, the European Public Assessment Report and Australia’s Public Assessment Report for the same product. Compared with the BR Template, existing regulatory report formats are inadequate regarding the listing of benefits and risks, the assigning of relative importance and values, visualization and the utilization of a detailed, systematic, standardized structure. The BR Template is based on the principles of BR assessment common to major regulatory agencies. Given that there are minimal differences among the existing regulatory report formats, it is timely to consider the feasibility of a universal template.